Quality Characteristics of Seaweed (Kappaphycus alvarezii) Transparent Solid Soap with Different Glycerine Concentrations - Dini Surilayani; Enis Sumarni; Ririn Irnawati (Jurnal Perikanan dan Kelautan, 2019)
Soap is a form of cosmetic preparation that is in demand by the public for the skin. This study aims to determine the optimum concentration of glycerin and determine the characteristics of transparent solid soap of seaweed produced. The research was carried out in April-October 2018. The making of soap uses three different of glycerin concentration (49 g, 59 g and 69 g). Based on the results of the study, seaweed transparant solid soap in accordance with Indonesian National Standarization 2016, except water content. Water content are 29.70%, 29.87%, and 39.77%. The best results for free fatty acid level testing were at glycerin concentration 59 g of 0.07%, the best results from non-soapy numbers were at glycerin concentration of 49 g and 69 g of 0.16%. The results of sensory analysis showed that the addition of glycerin 59 g was the best result based on the panelist's evaluation of the transparency parameter, while for the best impression the net concentration was based on the panelist's assessment of the addition of glycerin 49 g.